Understanding the factors influencing motorcycle ownership and use frequency in developing cities (2022)
The growing popularity of the motorcycle in major Latin American cities has brought new challenges for transportation and urban planning since the massive use of this vehicle causes substantial negative externalities, like a high rate of accidents and the augmentation of traffic congestion and pollution. However, after reviewing the literature looking to identify the key factors that explain this popularity, it was noticed that insufficient information was available to understand this phenomenon, particularly in Latin America. Thus, this study aimed to understand the factors that motivate the upward tendency of owning a motorcycle in large Latin American cities and explore the reasons for using this vehicle with a medium or high frequency, for commuting trips. To do so, an online survey was applied to a strati?ed random sample of motorcycle and non-motorcycle users from Bogotá, Colombia. Using this data, two hybrid choice models incorporating latent variables were estimated to identify the elements that influence individuals¿ utility. Considering the shortage of previous information, this study used an exploratory approach to find out if, besides the traditional sociodemographic variables used for modelling this type of decisions, other elements could be motivating motorcycle users. Results reveal that both decisions are a combination of sociodemographic and built environment attributes, but that attitudes and perceptions of the individual also influence the decisions. For example, having a negative perception of public transportation, a pro-motorcycle personality and a motorcycle habit are key determinants for deciding to own and use frequently this vehicle. The results of this study contribute to enriching the literature about motorcycle ownership and use in developing countries and serve as a benchmark to design public policies aimed to achieve more sustainable cities.